Osteoinductive and Osteogenic Capacity of Freeze-Dried Bovine Bone Compared to Deproteinized Bovine Bone Mineral Scaffold in Human Umbilical Cord Mesenchymal Stem Cell Culture: An In Vitro Study - Nugraha, Andreas Pratama; Kamadjaja, David B.; Sumarta, Ni Putu Mira; Rizqiawan, Andra; Pramono, Coen; Yuliati, Anita; Hendrianto, Eryk; Rahman, Mohammad Zeshaan (European journal of dentistry, 2023)
Objective Freeze-dried bovine bone scaffold (FDBB) or decellularized FDBB (dc-FDBB) was developed as an ideal scaffold with osteoinductive properties. This research aims to compare the osteoinductive properties marked by the expression of runt-related transcription factor-2 (RUNX2) and Osterix (OSX) and the osteogenic capacity of these scaffolds imbued with human umbilical cord mesenchymal stem cells (hUCMSCs). Materials and Methods This study was performed in five experimental groups: a negative control group (C-) of hUCMSCs with a normal growth medium, a positive control group (C + ) of hUCMSCs with an osteogenic medium, experimental group 1 (E1) with an FDBB conditioned medium (CM), and experimental group 2 (E2) with a dc-FDBB-CM, and a third experimental group (E3) consisting of a DBBM-CM. Alizarin red staining was performed to qualitatively assess osteoinductive capacity. RUNX2 and OSX expression was quantified using real-time quantification polymerase chain reaction with two replications on day six (D6) and day 12 (D12) as fold changes. Results This experiment revealed that hUCMSCs were positively expressed by CD73, CD90, and CD105 but were not expressed by CD34. Alizarin red staining showed that E1 had the most calcium deposition on D6 and D12, followed by E3 and then E2 The RUNX2 and OSX expression was higher in E1 but this difference was not significant. The OSX expression in E1,E2,E3 was lower on D12 and C+ of OSX had the highest expression. There was a significant difference of fold change measured between all groups (p < 0.05), and there was no significant difference between any of the groups treated with OSX and RUNX2 on D6 and D12. Conclusion FDBB osteoinduction and osteogenic capacity were higher when compared with DBBM and dc-FDBB.